Characterization, antioxidant and α-glucosidase inhibitory activity of collagen hydrolysate from Lamuru (Caranx ignobilis) fishbone - Syamsu, Nur; Wierson, Yogillverd; Yulia,; Sami, Fitriyanti Jumaetri; Megawati,; Nur Aisyah, Andi; Marwati,; A. Gani, Sahibuddin (Penerbit Universiti Kebangsaan Malaysia, 2021)
The Lamuru fish (Caranx ignobilis) is mostly found in tropical waters of the indo-pacific region, namely Indonesia. It is believed to contain collagen and this study aims to isolate collagen from its bone and determine the collagen’s antioxidant and α-glucosidase inhibitory activity. In our study, the collagen was extracted using acetic acid which was hydrolyzed by collagenase enzyme from Clostridium histolyticum at a temperature of 37 °C, and pH 7.0. During hydrolysis, the degree of hydrolysis (DH) was calculated and collagen hydrolysates were characterized by SDS-PAGE, UV-Visible spectroscopy and FT-IR spectroscopy. After characterization, the collagen hydrolisate of lamuru (CHL) fish was analyzed for its antioxidant properties and α-glucosidase inhibitory activity. The result shows that a higher percentage degree of hydrolysis was obtained, 31.17%, at 120 min of hydrolysis. The CHL characterization by SDS-PAGE showed its molecular weight ranging from 35,000-180,000 Daltons and identified the collagen as type I. The UV-Vis analysis of CHL provided a maximum absorbance at a wavelength of 233 nm. At the same time, the FT-IR analysis showed the presence of amides I, II, and III, which confirms the formation of the collagen triple helix. For its bioactivity assay, the CHL shows that CHL provided DPPH radical reduction activity reaching 51.45±1.24% (IC50 at 485.9 μg/mL). The ferric reduction antioxidant power of CHL (FRAP value) showed a significant reduction of Fe3+ to Fe2+ with a value of 711.27 μM/g. The CHL inhibition activity of α-glucosidase enzyme IC50 was determined to be 574 μg/mL. Based on the antioxidant bioactivity and α-glucosidase inhibition, the collagen peptide enables its use as a therapeutic development for a variety of disorders caused by oxidative stress, such as diabetes mellitus.